2014
DOI: 10.1007/s13753-014-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Environmental Hazards on the Great Hungarian Plain, Carpathian Basin

Abstract: The potential impacts of climate change on the Great Hungarian Plain based on two regional climate models, REMO and ALADIN, were analyzed using indicators for environmental hazards. As the climate parameters (temperature, precipitation, and wind) will change in the two investigated periods (2021-2050 and 2071-2100), their influences on drought, wind erosion, and inland excess water hazards are modeled by simple predictive models. Drought hazards on arable lands will increasingly affect the productivity of agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
2
29
0
3
Order By: Relevance
“…Which drought index is most appropriate to develop an understanding of coniferous tree ring growth in response to dryer conditions across the SWUS? A number of drought indices have been produced for monitoring or assessing the spatial patterns and temporal trends of droughts (Du Pisani et al 1998, Heim 2002, Keyantash and Dracup 2002, Mezősi et al 2014, including (i) the PDSI (Palmer 1965, Dai 2011a, 2011b that is based on a soil water balance equation; (ii) the standardized precipitation index (McKee et al 1993) that is based on a precipitation probabilistic approach; (iii) dryness (Budyko 1969, Zhou et al 2008, Yi et al 2010 that is based on annual energy and water budgets; (iv) forest droughtstress index derived from tree-ring data which is influenced by warm-season vapor-pressure deficit and cold-season precipitation (Williams et al 2013); and (v) the standardized precipitation evapotranspiration index (SPEI) indicates deviation from the average water balance (precipitation minus potential evapotranspiration) (Vicente-Serrano et al 2010). Here, we use the SPEI as a drought variable for data analysis because the SPEI data are available for different timescales representing the cumulative water balance over the previous n months and also incorporates the effects of temperature on drought severity (Beguería et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Which drought index is most appropriate to develop an understanding of coniferous tree ring growth in response to dryer conditions across the SWUS? A number of drought indices have been produced for monitoring or assessing the spatial patterns and temporal trends of droughts (Du Pisani et al 1998, Heim 2002, Keyantash and Dracup 2002, Mezősi et al 2014, including (i) the PDSI (Palmer 1965, Dai 2011a, 2011b that is based on a soil water balance equation; (ii) the standardized precipitation index (McKee et al 1993) that is based on a precipitation probabilistic approach; (iii) dryness (Budyko 1969, Zhou et al 2008, Yi et al 2010 that is based on annual energy and water budgets; (iv) forest droughtstress index derived from tree-ring data which is influenced by warm-season vapor-pressure deficit and cold-season precipitation (Williams et al 2013); and (v) the standardized precipitation evapotranspiration index (SPEI) indicates deviation from the average water balance (precipitation minus potential evapotranspiration) (Vicente-Serrano et al 2010). Here, we use the SPEI as a drought variable for data analysis because the SPEI data are available for different timescales representing the cumulative water balance over the previous n months and also incorporates the effects of temperature on drought severity (Beguería et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to climatic forces will tend to continue (Bartholy et al, 2011;Blanka et al, 2013;Mezősi et al, 2014) that is why the more ex- Fig. 7 Spatial distribution of correlations between pine (green), black locust (red) and poplar (orange) samples and aridity indices in the case of PAI (a) and FAI (b), and spatial distribution of mean ring width sensitivity (c)…”
Section: Discussionmentioning
confidence: 99%
“…drought, inland excess water, high magnitude flood (Pálfai and Herczeg, 2011;Mezősi et al, 2014). According to regional climate model predictions, more areas will face increasing temperature and changing precipitation conditions (Bartholy, 2011;Blanka et al, 2013), and the further increase of the hydroclimatic extremes is also projected (Mezősi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that out of the natural parameters, first the change in the amount of precipitation and second the altitude of the landscape, should be considered to specify that a slight decreasing trend in annual precipitation is confirmed between 1950 and 2010 for the investigated area (Mezősi et al, 2014). From the same study in the same time period, with steadily increasing temperature and evaporation, no increase in the water supply is predicted in the long term.…”
Section: Fig 2: Change Of Groundwater Levels In May (Cm); the Averagmentioning
confidence: 95%